THE EFFECT OF MACROECONOMIC VARIABLES ON THE COMBINED STOCK INDEX IN THE INDONESIA STOCK EXCHANGE - Marinus Ronal; Jens Batara Marewa; Willy Yavet Tandirerung (Jurnal Ekonomi, 2023)
This study aims to determine the correlation of Macroeconomic variables such as Inflation, Interest Rates, Exchange Rate, Money Supply and Gross Domestic Product with the Composite Stock Price Index registered on the Indonesia Stock Exchange (IDX). The analytical approach used is the classical assumption test, multiple linear regression, and hypothesis testing. The population in this study is the non-sectoral stock index on the Indonesia Stock Exchange and the sample in this study is the composite stock price index. The results of the study found that inflation (X1) and the money supply (X4) were positively correlated but not significant and interest rates (X2) were negatively correlated but not significantly related to the Composite Stock Price Index (Y). There is also the exchange rate (X3) which has a negative and significant effect and Gross Domestic Product (X5) which has a positive and significant effect on the Composite Stock Price Index (Y). The results of the study using the Coefficient of Determination method have a value of 0.832 or 83.2% which indicates a strong relationship between the macroeconomic variables and the Jakarta Composite Index.